2009
DOI: 10.1021/ac9014353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Carbohydrates and Steroids by Cation-Enhanced Nanostructure-Initiator Mass Spectrometry (NIMS) for Biofluid Analysis and Tissue Imaging

Abstract: Nanostructure-initiator mass spectrometry (NIMS) is a highly sensitive, matrix-free technique that is well suited for biofluid analysis and imaging of biological tissues. Here we provide a new technical variation of NIMS to analyze carbohydrates and steroids, molecules that are challenging to detect with traditional mass spectrometric approaches. Analysis of carbohydrates and steroids was accomplished by spray depositing NaCl or AgNO3 on the NIMS porous silicon surface to provide a uniform environment rich wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 73 publications
1
77
0
Order By: Relevance
“…NIMS-IMS allows a direct characterization of peptide microarrays, direct mass analysis of single cells, tissue imaging, and direct characterization of blood and urine. [147][148][149][150] Liu et al demonstrated the use of a hybrid ionization approach, matrix-enhanced surface-assisted laser desorption/ionization mass spectrometry (ME-SALDI-MS), in IMS. 151,152 In ME-SALDI, the combination of MALDI with SALDI enables the successful IMS of low-mass species with improved detection sensitivity.…”
Section: Saldi-ms For Imaging Mass Spectrometrymentioning
confidence: 99%
“…NIMS-IMS allows a direct characterization of peptide microarrays, direct mass analysis of single cells, tissue imaging, and direct characterization of blood and urine. [147][148][149][150] Liu et al demonstrated the use of a hybrid ionization approach, matrix-enhanced surface-assisted laser desorption/ionization mass spectrometry (ME-SALDI-MS), in IMS. 151,152 In ME-SALDI, the combination of MALDI with SALDI enables the successful IMS of low-mass species with improved detection sensitivity.…”
Section: Saldi-ms For Imaging Mass Spectrometrymentioning
confidence: 99%
“…Therefore, the use of NIMS for tissue imaging in negative ionization mode will likely become a reality soon. NIMS surface can be further modified by coating the nanopores with cationization agents such as NaCl or AgNO 3 Adapted from reference [25] and [26], Copyright 2012, with permission from American Chemical Society and Elsevier, respectively. [25].…”
Section: Nims Surface Modificationsmentioning
confidence: 99%
“…MS analysis methods. In addition to analysis of the model peptide sample (des-Arg 9 -Bradykinin) presented in this study, other samples, such as proteins [12][13][14], peptides [1,2,7,11], polymers [15,16], tissue [17,18] and abuse drugs [19] can be analyzed using the nSi-MS platform. Investigation of various small molecules to the nanostructured silicon surface interactions are detail discussed in our recent published paper [20].…”
Section: Nsi-ms D/i Efficiencymentioning
confidence: 99%